Factor Structure and Validation of the Undergraduate Teaching Faculty Investment Questionnaire - Sun, Lizhi; Zhang, Hong; Xu, Jingjing (Frontiers in Psychology, 2021)
Undergraduate education is very important for higher education. Among the factors affecting the quality of undergraduate education, teaching quality is the most important factor. At present, an important reason that affects the teaching quality is insufficient teaching investment. An open-ended questionnaire survey was conducted on 62 faculty members and 65 university students in China, and it was found that undergraduate teaching investment of faculty members mainly consists of four parts: workload investment, ability investment, energy investment and teaching emotional investment. A preliminary test was conducted on 342 faculty, and the results of exploratory factor analysis supported the proposed four-dimensional teaching investment model. The formal test was completed for 293 faculty. The confirmatory factor analysis showed that the four-dimensional model has a good degree of fit. A further criterion-related test showed that the four-dimensional teaching investment of faculty members has a significant positive correlation with classroom management, clarity of teaching materials, teacher-student interaction, teaching strategies and skills application, and work engagement. The research results shows that the four dimensions of teaching investment can effectively measure the teaching investment of faculty members, specify the indicators of teaching investment, and promote the development of faculty teaching investment research.